2018
DOI: 10.1103/physrevfluids.3.114201
|View full text |Cite
|
Sign up to set email alerts
|

Temperature gradient induced double stabilization of the evaporation front within a drying porous medium

Abstract: This is an author's version published in: http://oatao.univ-toulouse.fr/21468 To cite this version:Vorhauer, Nicole and Tsotsas, Evangelos and Prat, Marc Temperature gradient induced double stabilization of the evaporation front within a drying porous medium. (2018) Physical Review Fluids (3). 1-24. ISSN 2469-990X Official URL:https://doi.Drying of porous media very often occurs in the presence of significant temperature gradients because heat fluxes are imposed in many situations in order to decrease the dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…There also exists a number of PNMs that additionally incorporate pore scale mechanisms, such as liquid film flow [15][16][17] or crystallization [18][19][20]. Only a few models are available that take into account coupled heat and mass transfer [21,22] or that at least consider the invasion and transport processes under non-isothermal conditions [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…There also exists a number of PNMs that additionally incorporate pore scale mechanisms, such as liquid film flow [15][16][17] or crystallization [18][19][20]. Only a few models are available that take into account coupled heat and mass transfer [21,22] or that at least consider the invasion and transport processes under non-isothermal conditions [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These authors revealed that liquid film rings can develop in systems with heterogeneous wetting properties and limited interconnection of the solid, such as in a 2D microfluidic device (as investigated in Vorhauer et al [13] ) or 3D glass bead packings. [2,15] The specific strength of the pore scale model is also revealed in face of the nonisothermal drying experiments studied in Vorhauer et al, [12] where the pore network is simultaneously invaded by the gas-phase (as a result of evaporation) and the liquid phase (as a result of condensation). This phenomenon is also expected in a wide range of other applications, such as the simultaneous drainage and imbibition in gas diffusion layers (GDL), in fuel cells usually affected by thermal gradients.…”
Section: Introductionmentioning
confidence: 89%
“…This is a completely different situation than in the isothermal simulation where the evolution of the liquid distribution in the TPM is controlled by the external vapor mass transfer structure. According to discussions in Vorhauer et al [12] it is strongly expected that thickness of the annular traveling zone (in case of a radial thermal gradient) depends on the magnitude of the temperature gradient and the overall evaporation rate as well. This is highlighted in Fig.…”
Section: Study Of the Thermal Impact Of Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when the throat size distribution becomes broader, the invasion follows the path of the least resistance, which results in a more random distribution of the phase patterns, provided that the throat sizes are randomly distributed. Following [60] and [61], the occupation probability decreases with growing ∆r.…”
Section: Bimodal Pore Size Distributionsmentioning
confidence: 99%